14th AIAA/CEAS Aeroacoustics Conference (29th AIAA Aeroacoustics Conference) 2008
DOI: 10.2514/6.2008-2911
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Demonstration of the New Virginia Tech Anechoic Wind Tunnel

Abstract: A unique new removable anechoic system and new acoustic treatment for the Virginia Tech Stability Wind Tunnel is described. The new system consists of a Kevlar-walled acoustic test section flanked by two anechoic chambers. In its new configuration the facility is closed aerodynamically and open acoustically, allowing far-field acoustic measurements with a flow quality comparable to that of a hardwalled wind tunnel. An extensive program of experiments has been conducted to examine the performance of this new ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 3 publications
0
24
0
2
Order By: Relevance
“…Some of the tunnels are of closed-circuit design [1][2][3][4][5] with a closed or semi-closed test section, where the air flow from the nozzle enters a collector. The others are open circuit tunnels [6][7][8][9][10] where the open jet from the nozzle is not collected, but expands freely into a larger room.…”
Section: Wind Tunnel Layoutmentioning
confidence: 99%
“…Some of the tunnels are of closed-circuit design [1][2][3][4][5] with a closed or semi-closed test section, where the air flow from the nozzle enters a collector. The others are open circuit tunnels [6][7][8][9][10] where the open jet from the nozzle is not collected, but expands freely into a larger room.…”
Section: Wind Tunnel Layoutmentioning
confidence: 99%
“…A very well known aeroacoustic wind tunnels is in the Virginia Tech of the United States 1 . The 1.83 m x 1.83 m test section can achieve maximum speed of about 75 ms -1 without blockage.…”
Section: Introductionmentioning
confidence: 99%
“…This subsonic wind tunnel utilizes a continuous, single return design and is capable of achieving speeds in excess of 80-m/s in the test section. Upgrades to the test section and wind tunnel circuit (Smith, et al 2005, Crede 2008, Remillieux, et al 2008) allow this facility to run in an anechoic configuration that has been shown to be acoustically quiet while still maintaining favorable aerodynamics (Remillieux, et al 2008, Devenport, et al 2010. The flow entering the test section has been found to have turbulence levels of 0.021% at 21-m/s and 0.031% at 57m/s.…”
Section: Virginia Tech Stability Wind Tunnelmentioning
confidence: 99%
“…The fan consists of 8 Clark-Y airfoil section blades and can be driven at over 600-RPM. A foam fan liner has been applied to reduce the tip gap and tip noise by almost 6-dB across the entire frequency range (Remillieux, et al 2008). Downstream of the fan, the flow enters an air exchange tower which is partially open to the atmosphere.…”
Section: Virginia Tech Stability Wind Tunnelmentioning
confidence: 99%